Implementasi Augmented Reality Pengenalan Tokoh Pahlawan dan Tarian pada Uang Kertas Rupiah - Eldayanti, Putri Elvina; Feoh, Gerson; Rahayu, Prastyadi Wibawa (LPPM UNIKA Santo Thomas Medan, 2024)
This research is motivated by the need for more interactive and interesting learning media in introducing the history of heroes and traditional dances contained in the 2022 emission rupiah banknotes to 5th grade students at SDS Wahidiyah Denpasar. Augmented Reality (AR) application based on marker-based tracking was developed to visualize 3D objects of heroes and dances interactively through Android smartphones. The results showed that the use of AR applications significantly improved student understanding, with an average pre-test score of 47.81 points which increased after the application was used in the learning process. Hopefully, the results of this research will not only increase students' interest and understanding of national history, but also encourage innovation in learning methods in elementary schools through the use of AR technology.